2023
DOI: 10.54012/jurnalinsancendekia.v4i1.133
|View full text |Cite
|
Sign up to set email alerts
|

Metode Pendidikan Perspektif Tafsir Tarbawi

Abstract: Penelitian ini berusaha untuk mengkaji ayat-ayat Al Quran yang berhubungan dengan metode pendidikan, kajian ini semacam ini disebut juga Tafsir Tarbawi. Latar belakang penelitian ini adalah saat ini masih banyak pendidik yang belum menyadari bahwa Al Quran juga menkaji tentang masalah pendidikan, sehingga mereka lebih condong mengambil referensi dari buku-buku yang sebenarnya tidak ada kaitannya dengan ke-Islaman, untuk itu kami menyusun jurnal yang mengkaji metode, pendidikan dari sudut pandang kajian Tafsir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Targhib means fun and tarhib means to scare, namely the method of giving rewards and punishments, or in other editorials it is often called reward and punishment (Suyati et al, 2023). With this method, teachers can reward students who excel by giving punishment to students who break the rules (Firdaus, 2020).…”
Section: Targhib Wa Tarhib Methods 311 Definitiomentioning
confidence: 99%
See 1 more Smart Citation
“…Targhib means fun and tarhib means to scare, namely the method of giving rewards and punishments, or in other editorials it is often called reward and punishment (Suyati et al, 2023). With this method, teachers can reward students who excel by giving punishment to students who break the rules (Firdaus, 2020).…”
Section: Targhib Wa Tarhib Methods 311 Definitiomentioning
confidence: 99%
“…So it can be concluded that the targhib wa tarhib method is a method presented in the Qur'an to stimulate students' thinking patterns and encourage students' motivation towards goodness because as understood by Targhib which means the promise of pleasure in the afterlife in heaven and Tarhib which means punishment for sinners there will be misery in the afterlife in hell (Mawaddah, 2018). With this method, teachers can reward students who excel by giving punishment to students who break the rules (Suyati et al, 2023).…”
Section: Targhib Wa Tarhib Methods 311 Definitiomentioning
confidence: 99%